From “Catholic Nation” to “Pluricultural Republic” in Latin America. Some historical considerations (2012)
This text is a historical analysis of how the “Catholic nation” in Latin America was the result of a difficult construction process in the nineteenth century and first half of the twentieth century, and on the transition from “Catholic nation" to “multicultural republic” in many Latin American countries in the last third of the twentieth century.